Tourist Safari: Learning based on the methods of projects such as the ‘hands-on’ approach in building knowledge for the students in course LM-0347 (Panorama of Tourism in French IV), School of Modern Foreign Languages - Macías Alvarenga, Ivannia (2023)
This article will report the results derived from implementing a hands-on approach for students in course LM-0347 in the Undergraduate Degree in French. This method has the primary aim of promoting the student as the active builder of their own learning. Secondly, it promotes the importance of incorporating the theory and the practical applications of this approach, through a unique simulation made for this course, which permits the student to acquire and apply the skills in this topic, without setting aside the linguistic side of the content. Thirdly, it will develop their independence and prepare them for a professional career in the tourism industry.